STUDI LITERATUR : RASIONALITAS PENGGUNAAN ANTIPSIKOTIK PADA PASIEN GANGGUAN KEJIWAAN SKIZOFRENIA - Adin Hakim Kurniawan; Yetri Elisya; Muhamad Irfan (Jurnal Insan Farmasi Indonesia, 2020)
People with severe mental disorders are people with acute psychotics and schizophrenia. Schizophrenia is a severe mental disorder, characterized by many disturbances in thinking, affecting language, perception, and a sense of self-awareness. Drug rationality is the use of rational drugs where patients receive treatment that corresponding clinical needs. The results of Basic Health Research in 2013 and 2018 showed an increase in the prevalence of ODGJ of 5.3%. The main purpose of this research to To find out the rationality antipsychotic use in schizophrenic psychiatric patients. Thisresearch design used was a literaturestudy, articles were collected using the GoogleSchoolar database. The results showed that there werepatients who have schizophrenia are men with an age range of 18-45 yearswith a Antipsychotic classification. Typical.Classification single therapeutic classusing haloperidol and combination therapy class using chlorpromazine and Haloperidol.as well as having good rationality based on the right indication, the right medicine, the right patient, the right dose.